EVALUASI PELAKSANAAN PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI KABUPATEN DHARMASRAYA - Inggriani "; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The aid stimulant innate strength housing (BSPS) is government facility, that is a number of donation that offered for society who have low salary. Meanwhile, innate strength Development is the building of housing because of initiative and society exertion with according to individual or group, include of repair, restoration or boarden, build of new house and environment.Purpose this research to do evaluation of implementation aid innate strength Development (BSPS) in Dharmasraya regency and to know factors that influence of implementation this program.The teory concept that used by researcher are evaluation teory and evaluation of program according Hanif Nurcholis. This research is kind of qualitative research with investigate of data according to descriptive. In the collect research data use interview technique, observation and documentation use key informant as information source.The result of this research indicate evaluation of implementation aid innate strength Development (BSPS) in Dharmasraya regency not optimal yet. Factors that influence this implementation because minus resource, implementation, communication, dispotition and bureaucracy structure.Keyword: evaluation of programs, aid stimulant innate strength development, evaluation teor.